Pretrial Proceedings in Indonesian Criminal Procedure Law: Its Relation to Corruption Eradication - Adiatma Nugroho; Beniharmoni Harefa; Handar Subhandi Bakhtiar (International Journal of Social Science and Humanity, 2025)
Pretrial proceedings play a strategic role in Indonesia's criminal justice system as a judicial oversight mechanism to ensure the legality of law enforcement actions and the protection of suspects’ human rights. In corruption cases, however, pretrial motions are often exploited as procedural loopholes to invalidate ongoing investigations due to the absence of rigid legal standards and inconsistent interpretations by judges sometimes extending into the merits of the case, which should fall outside the scope of pretrial jurisdiction. This study examines the ideal concept of pretrial review using a normative juridical approach, emphasizing the due process of law principle, the primacy of lex specialis under Article 26A of the Anti-Corruption Law, and its harmonization with the Criminal Procedure Code (KUHAP). The research concludes that pretrial mechanisms should function solely as limited judicial review, restricted to evaluating procedural legality. Additionally, the study highlights the significance of establishing Preliminary Examination Judges (Hakim Pemeriksa Pendahuluan) as proposed in the Draft Criminal Procedure Code. These judges would proactively supervise investigative actions, ensuring procedural compliance and minimizing the misuse of pretrial remedies by corruption suspects. Strengthening normative frameworks and judicial guidelines is thus essential to foster coherent, fair rulings and support the integrity and effectiveness of anti-corruption law enforcement.